Ai-driven industry-education integration: empowering vocational education through information technology for innovative practical teaching - Meng, Y. (БНТУ, 2025)
The integration of next-generation digital technologies with industry, academia, and research can promote collaborative innovation and practical teaching. Meanwhile, China-Belarus digital economy cooperation is a significant driving force for the modernization of cross-border higher education.